Crecimiento economico e inversion extranjera directa en Ecuador, periodo 2000-2020. - Moreira Cedeño, Maria Vanessa; Vera Cedeño, Jonathan Josue (My University, 2021)
The relationship between foreign direct investment and economic growth, as well as private investment, are indicators of interest to economic analysts because these variables are considered an important source of financing for countries that are in the process of development, with the purpose of reactivating the economy through the acquisition of technology, in order to improve production processes and at the same time increase the training of human talent. The objective of this descriptive study is to analyze the incidence of foreign direct investment and gross fixed capital formation variables as a function of Ecuador's gross domestic product, through an equilibrium analysis in the long and short term during the period 2000-2020. For this purpose, an econometric model of cointegration and error correction mechanism was developed through an autocorrelation analysis in time series using STATA 15 statistical software. The results showed cointegration in the short and long term between the variable gross fixed capital formation and gross domestic product, in addition, foreign direct investment presented an equilibrium relationship in the long term as a function of economic growth, concluding that foreign direct investment has a moderate contribution but is not so influential to the country's economic growth.
La relación entre la inversión extranjera directa y el crecimiento económico, así como la inversión privada son indicadores de interés para analistas económicos debido a que estas variables son consideradas como una importante fuente de financiamiento para países que están en proceso de desarrollo, con la finalidad de reactivar la economía mediante la adquisición de tecnología, para así mejorar los procesos de producción y a su vez incrementar la capacitación del talento humano. El objetivo de este estudio descriptivo es analizar la incidencia que presentaron las variables de inversión extranjera directa y formación bruta de capital fijo en función al producto interno bruto del Ecuador, mediante un análisis de equilibrio en el largo y corto plazo durante el periodo 2000-2020. Para esto se desarrolló un modelo econométrico de cointegración y mecanismo de corrección de errores, a través de un análisis de autocorrelación en series de tiempo utilizando el software estadístico STATA 15. Los resultados mostraron la cointegración en el corto y largo plazo entre la variable formación bruta de capital fijo y el producto interno bruto, además la inversión extranjera directa presentó una relación de equilibrio en el largo plazo en función al crecimiento económico, concluyendo que la inversión extranjera directa tiene una aportación moderada pero no es tan influyente al crecimiento económico del país.
Keywords: CRECIMIENTO ECONÓMICO; FBKF; IED; INVERSIÓN PÚBLICA